Primary, secondary and tertiary teachers of English: their beliefs about their learners - Díaz-Larenas, Claudio (2015)
As reflective practitioners, teachers build their own pedagogical beliefs about teaching and learning and particularly about the role played by students in language learning. This study aims to identify the pedagogical beliefs held by a group of thirty Chilean primary, secondary and tertiary teachers of English about the role of students in the teaching process. A survey, a semi-structured interview, a journal and five class observation journals were employed to uncover the participants’ beliefs. The data were analyzed through the qualitative data analysis program ATLASTI that led to the construction of three dimensions and ten categories, through the use of the semantic content analysis technique. The results show that the three groups of teachers declare that students who learn a foreign language should possess personal and academic characteristics related to motivation, participation and autonomy, among others; however, at the classroom those students assume a passive and reactive role towards the highly structured teaching environment created by the teacher. In conclusion, teacher beliefs are fed by theory and corroborated or questioned by classroom practice as a bidirectional relationship between theory and practice and vice versa.